The role of financial advisers in Malaysian mergers and acquisitions (M&As) / Song Saw Imm and Erimalida Yazi - Imm, Song Saw; Yazi, Erimalida (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2011)
Literature in the field of M&A shows that acquirers did not gain from the transaction and the successful rate of takeover was quite low at about 40% in the 1970s and about 60% in the 1990s. So, this study aims to investigate the effects of engaging financial advisers in merger and acquisition (M&A) transactions. It measures whether different tiers of financial advisers with different expertise, experience and information bring different outcome towards their clients' firms in terms wealth effect. Commonly, the choice of financial advisers to provide M&A advice was essentially determined by their perceived quality or reputation. The determination of the adviser quality was based on the annual adviser league table according to the market share of the advisers for the twelve-month period. Flexible ranking method was used in order to differentiate the quality of advisers. Using flexible ranking method, the financial advisers are ranked every year based on the market share in that particular year. First tier advisers are ranked by 1/3 of the highest market share. Second tier advisers who control another 1/3 of the market share. The rest are third tier advisers. All data were subtracted from Thomson ONE Banker Database. The results from using a three-tier classification method and ranked using the flexible ranking technique showed financial advisers were not significant in determining the wealth effect of the clients. One possible reason is that using financial advisers is not a popular choice among the potential M&A firms